Autocratic Dialectics: Mythological Reconfiguration of Leaders and the Collapse of Democracy in the Republic Of Serbia - Muedib Šahinović (Društvene i Humanističke Studije)
The paper presents a socio-political analysis of the complex process of democratization in the Republic of Serbia, which had its ups and downs in the late 20th and early 21st centuries. Analyzing some of the failures of the democratic forces, which enabled the unexpectedly quick return of autocratic leaders and their ideas to the political scene of Serbia, it was necessary to deconstruct the specific role of the leader who has mythological attributions and unites unlimited ruling power in his supremacy. The analysis of the authoritarian elements of the government includes a case study of the dependent judiciary (the focus is on the prosecution), which is under the complete control of the ruling political structure and figures as a tool in the hands of the leaders. During the research, qualitative methods were used along with the analysis of several key indicators that point to the systematic collapse of democracy, the suspension of human rights and the restriction of freedoms. The results of the research confirm that a specific model of formal democracy and essential autocracy has been generated in the Republic of Serbia, which exists within a unique political system and has been very successfully maintained in power for more than a decade.